From fads to facts: a systematic review and meta-analysis of intermittent pneumatic compression therapy for muscle recovery - Albillos-Almaraz, L.; Cavero-Redondo, I.; Rodríguez, M. Á.; Fares, R.; Crespo, I.; del Valle, M.; Olmedillas, H. (Strength and Conditioning Journal, 2025)
Recovery is essential for athletic performance and injury prevention. Athletes use intermittent pneumatic compression (IPC) to aid muscle fatigue recovery, but its efficacy is unclear. A meta-analysis was conducted to assess the effectiveness of IPC on the recovery of muscle fatigue. A systematic search for related studies published from inception to August 2024 using the following databases was conducted: MEDLINE, EMBASE, CENTRAL, Web of Science, Scopus, SPORTDiscus, and PEDro. Twenty-seven studies (554 healthy adults) that compared IPC recovery and any other treatment after exercise-induced muscle damage (EIMD) were included. Each study used different EIMD protocols and a plethora of assessment instruments including performance tests, fatigue scores, soreness and pain score, and inflammatory markers. The meta-analysis showed that there were statistically significant small effects of soreness and pain (Effect Size (ES) = -0.45; 95% confidence intervals [CI]: -0.65 to -0.25) and creatine kinase values (ES = 0.36; 95% CI: 0.37-0.68). A nonstatistically significant effect was found for the rest of the variables (ES = -0.17-3.12). Therefore, although IPC seems effective in reducing pain and soreness, its effects on recovery after intense exercise remain inconclusive. The current evidence is limited and does not allow any definitive recommendations for clinical practice.